Do Risk-Taking and Shariah Governance Have a Relationship with Maqasid Shariah-Based Performance? - Prasojo Prasojo; Winwin Yadiati; Tettet Fitrijanti; Memed Sueb (Global Review of Islamic Economics and Business, 2022)
This According study examines the characteristics of the shariah supervisory board (SSB), risk-taking and Islamic bank (IB) performance. The maqasid shariah index determines the performance of an IB, and the performance assessment is more comprehensive. This research data analysis uses the dynamic panel regression estimation technique with the generalised two-step moment method to predict the relationship between shariah governance, risk-taking and performance. This study uses IBs financial data from around the world for 2014–2018, which comes from the bank scope database. The empirical results found that risk-taking has positive significance to maqasid shariah, while SSB size, expertise and cross membership have a significant negative relationship to performance. Other variables, such as leverage, are proven to have negative significance to maqasid shariah. The originality of this research is linking maqasid shariah with risk-taking and governance, expanding the sample to include many countries, and robustness checking based on Gulf Cooperation Council and non-GCC member states. The research has implications for stakeholder theory because IBs can accommodate various stakeholder interests. Governance across countries is not uniform, so it is challenging to link specifically to performance.